Gene expression profiling of serrated polyps identifies annexin A10 as a marker of a sessile serrated adenoma/polyp. Issue 4 (9th July 2013) - Gonzalo, David Hernandez; Lai, Keith K; Shadrach, Bonnie; Goldblum, John R; Bennett, Ana E; Downs‐Kelly, Erinn; Liu, Xiuli; Henricks, Walter; Patil, Deepa T; Carver, Paula; Na, Jie; Gopalan, Banu; et al.
Abstract Sessile serrated adenomas/polyps (SSA/Ps) are precursors of colon cancer, particularly those that exhibit microsatellite instability. Distinguishing SSA/Ps from the related, but innocuous, microvesicular hyperplastic polyp (MVHP) can be challenging. In this study seven gastrointestinal pathologists reviewed 109 serrated polyps and identified 60 polyps with histological consensus. Microarray analysis was performed on six distal consensus MVHPs < 9 mm, six proximal consensus SSA/Ps > 9 mm, and six normal colon biopsies (three proximal, three distal). Comparative gene expression analysis confirmed the close relationship between SSA/Ps and MVHPs as there was overlapping expression of many genes. However, the gene expression profile in SSA/Ps had stronger and more numerous associations with cancer‐related genes compared with MVHPs. Three genes (TFF2, FABP6, and ANXA10) were identified as candidates whose expression can differentiate SSA/Ps from MVHPs, and the differences in expression were confirmed by quantitative RT‐PCR. As ANXA10 showed the most promise in differentiating these polyps, the expression of ANXA10 was evaluated by immunohistochemistry in consensus SSA/Ps (n = 26), MVHPs (n = 21), and normal colon (n = 9). Immunohistochemical expression of ANXA10 was not identified in separate samples of normal colon or in the normal colonic epithelium adjacent to the serrated polyps. Consistent with the microarray and quantitative RT‐PCR experiments, immunohistochemical expression of ANXA10 was markedly increased in SSA/Ps compared to MVHPs (p < 0.0001). An ANXA10 score ≥ 3 has a sensitivity of 73% and a specificity of 95% in the diagnosis of an SSA/P. In conclusion, we show that SSA/Ps and MVHPs have significant overlap in gene expression, but also important differences, particularly in cancer‐related pathways. Expression of ANXA10 may be a potential marker of the serrated pathway to colon cancer. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.